ANALISIS NILAI MORAL DALAM TOKOH NOVEL “PULANG” KARYA SOFI MELONI - Margaretha, Tessa; Nuzulia Armariena, Dian; Masnunah, Masnunah (Parataksis: Jurnal Bahasa, Sastra, dan Pembelajaran Bahasa Indonesia, 2023)
The purpose of this research is to know and describe the moral values contained in the novel Pulang by Sofi Meloni. The research method used in this research is descriptive method. The data source of this research is the novel Pulang by Sofi Meloni. Data collection techniques in this study used documentation, while for data analysis techniques using content analysis techniques. Based on the results of the analysis, moral values in the form of human relationships with God are found, namely being grateful to God and surrendering to God and praying. In addition, moral values in the form of human relationships with themselves include: patience, responsibility, never giving up and working hard, accepting reality, sincerity, self-confidence, self-awareness, honesty, calmness, and optimism. Furthermore, moral values in the form of human relationships with other humans in the social sphere are giving advice to humans, helping, caring for others, and doing good. Keyword: Moral Value, Novel, Pulang